From gene to protein—experimental and clinical studies of ACE2 in blood pressure control and arterial hypertension - Patel, Sheila K.; Velkoska, Elena; Freeman, Melanie; Wai, Bryan; Lancefield, Terase F.; Burrell, Louise M. (Frontiers in Physiology, 2014)
Hypertension is a major risk factor for stroke, coronary events, heart and renal failure, and the renin-angiotensin system (RAS) plays a major role in its pathogenesis. Within the RAS, angiotensin converting enzyme (ACE) converts angiotensin (Ang) I into the vasoconstrictor Ang II. An “alternate” arm of the RAS now exists in which ACE2 counterbalances the effects of the classic RAS through degradation of Ang II, and generation of the vasodilator Ang 1-7. ACE2 is highly expressed in the heart, blood vessels and kidney. The catalytically active ectodomain of ACE2 undergoes shedding, resulting in ACE2 in the circulation. The ACE2 gene maps to a quantitative trait locus on the X chromosome in three strains of genetically hypertensive rats, suggesting that ACE2 may be a candidate gene for hypertension. It is hypothesised that disruption of tissue ACE/ACE2 balance results in changes in blood pressure, with increased ACE2 expression protecting against increased blood pressure, and ACE2 deficiency contributing to hypertension. Experimental hypertension studies have measured ACE2 in either the heart or kidney and/or plasma, and have reported that deletion or inhibition of ACE2 leads to hypertension, whilst enhancing ACE2 protects against the development of hypertension, hence increasing ACE2 may be a therapeutic option for the management of high blood pressure in man. There have been relatively few studies of ACE2, either at the gene or the circulating level in patients with hypertension. Plasma ACE2 activity is low in healthy subjects, but elevated in patients with cardiovascular risk factors or cardiovascular disease. Genetic studies have investigated ACE2 gene polymorphisms with either hypertension or blood pressure, and have produced largely inconsistent findings. This review discusses the evidence regarding ACE2 in experimental hypertension models and the association between circulating ACE2 activity and ACE2 polymorphisms with blood pressure and hypertension in man.